Constraints facing small medium and micro enterprises in Khayelitsha, Western Cape - Mbinda, Bukelwa (Cape Peninsula University of Technology, 2015)
The aim of this study was to determine the extent of constraints to entrepreneurial development in the townships supporting the Cape Town economy, specifically that of Khayelitsha, and to establish whether any government incentives were available to develop this township economy. These small, medium and micro sized businesses face numerous constraints. The vital role of small businesses in stimulating economic activity, in poverty alleviation, and in the raising of living standards, has been widely recognised in most countries. In fact, in several countries, small businesses are used as catalysts to generate economic activities within relatively poor communities. The City of Cape Town has developed economic initiatives to provide assistance to entrepreneurs with recommendations on how innovations should be encouraged to help entrepreneurs in such poor communities as Khayelitsha to start new businesses, and to create jobs. In order to obtain information on the Khayelitsha business community both qualitative and quantitative approaches were used. Questionnaires were employed to answer open and closed ended questions dealing with economic activities in the area, as well as interviews with formal and informal business persons. Generally, the findings reveal numerous constraints of trade facing businesses in Khayelitsha including governmental restrictions, lack of a skilled workforce, poor infrastructure, and services delivery. The recommendations made could lead to an improvement in operating conditions as this study argues that the existence of positive business conditions, in terms of social, economic, and personal factors, are necessary for business ventures and entrepreneurs to succeed. However, innovation is essential for small businesses to be able to respond effectively to the changing environment that has been triggered by globalisation forces.
Thesis (MTech (Business Administration))--Cape Peninsula University of Technology, 2015.
Keywords: Small business -- South Africa -- Khayelitsha -- Management; Entrepreneurship -- South Africa -- Khayelitsha; Khayelitsha (Cape Town, South Africa) -- Economic conditions; Economic development -- South Africa -- Khayelitsha